E-module for physics using Smart Apps Creator Software with internalization of soft skills - Armela, Kiki Rizki; Rosidin, Undang; Viyanti, Viyanti (Indonesian Journal of Science and Mathematics Education, 2024)
This study aims to develop an interactive e-module based on Smart Apps Creator software, focusing on the internalization of soft skills (creativity/innovation, problem-solving, teamwork, and personal effectiveness) in understanding the concepts of physics on work and energy material. The research method followed the 4-D development model but was limited to the development stage (Develop). The findings show that the developed e-module is deemed "feasible" based on evaluations by experts and educators, with an average score of 72% from the material experts, 94% from media experts, and 91% from educators. Furthermore, the e-module also received positive feedback from students with a score of 96% (highly feasible category). This study concludes that the developed e-module can be used as a physics learning medium to internalize soft skills. For future research, it is recommended that the effectiveness of this e-module be tested in various learning contexts and different student populations to broaden the understanding of its application and benefits in learning.